Degreasing and risk of non-Hodgkin lymphoma. Issue 8 (18th November 2008) - Purdue, M P; Severson, R K; Colt, J S; Stewart, P; De Roos, A J; Cerhan, J R; Cozen, W; Davis, S; Hartge, P; Schenk, M; Blair, A
Abstract : Objective: To investigate the relationship between selected solvent-related workplace tasks (degreasing, painting, gluing, stripping paint, staining) and risk of non-Hodgkin lymphoma (NHL). Methods: We analysed occupational data from a large population-based case-control study of NHL conducted in the USA. For participants reporting occupations with possible exposure to organic solvents, job-specific interview modules were administered to elicit in-depth information on solvent-related workplace tasks and other exposure-related factors (225 cases, 189 controls). Unconditional logistic regression models were fit to calculate odds ratios (ORs) and 95% CI for average frequency, maximal frequency and cumulative number of hours having performed each task. Individuals with jobs rated as unexposed to organic solvents in the workplace (180 cases, 213 controls) were used as a reference group. Results: We observed an increased risk of NHL among subjects in the highest category of maximal degreasing frequency (>520 h/year: OR 2.1, 95% CI 0.9 to 4.9, trend test p = 0.02). We found similar associations for the highest levels of average frequency and, among men, cumulative number of hours. Other solvent-related tasks were not associated with NHL. Conclusion: Findings from this case-control analysis of solvent-related tasks suggest that frequent degreasing work may be associated with an elevated risk of NHL.